2017
DOI: 10.1016/s2352-3026(17)30104-7
|View full text |Cite
|
Sign up to set email alerts
|

Allele-level HLA matching for umbilical cord blood transplantation for non-malignant diseases in children: a retrospective analysis

Abstract: Summary Background The standard for selecting unrelated umbilical cord blood units for transplantation for nonmalignant diseases rely on antigen-level (lower resolution) human leukocyte antigen (HLA) typing for HLA-A and –B and allele-level for HLA-DRB1. Our aim was to study the effects of allele-level matching at HLA-A, -B, -C and –DRB1, the standard for adult unrelated volunteer donor transplantation for nonmalignant diseases for umbilical cord blood transplantation. Methods We retrospectively studied 119… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
54
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 29 publications
9
54
0
1
Order By: Relevance
“…Interestingly, white children were more likely to receive better HLA-matched and race-matched CB units than black and other minority children. Several previous studies have shown better outcomes in patients receiving singleunit UCBT using better HLA allele-matched CB units [4]. The results of this study support the importance of increasing the collection of CB units from racial minorities; however, the decrease in the number of UCBTs performed annually has been accompanied by a significant reduction in the number of public CB banks.…”
supporting
confidence: 74%
“…Interestingly, white children were more likely to receive better HLA-matched and race-matched CB units than black and other minority children. Several previous studies have shown better outcomes in patients receiving singleunit UCBT using better HLA allele-matched CB units [4]. The results of this study support the importance of increasing the collection of CB units from racial minorities; however, the decrease in the number of UCBTs performed annually has been accompanied by a significant reduction in the number of public CB banks.…”
supporting
confidence: 74%
“…Conditioning regimen intensity was not associated with graft failure. Increased mortality and prevalence of graft failure after transplantation from HLA-mismatched unrelated donors has been reported for non-malignant diseases but those studies 21,22 did not include many patients who received transplants for haemoglobinopathies. Our findings confirm the adverse effect of HLA disparity on survival outcomes and graft failure after transplantation in patients with sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…109 Later reports confirmed the importance of counting matches at the high-resolution level for HLA-A, HLA-B, HLA-C, and HLA-DRB1 for malignant and nonmalignant diseases. 106,110 The incidence of neutrophil recovery was lower and graft failure and mortality rates were higher when the recipient and the CB unit were mismatched at $2 HLA highresolution types. In the setting of double CB unit transplantation, the same HLA match criteria that guide single-unit selection should be applied to the selection of both units.…”
Section: Hla Matching Requirements For Umbilical Cb Unitsmentioning
confidence: 99%